The TFP Channel of Credit Supply Shocks - Ben Zeev, Nadav (The Review of Economics and Statistics, 2023)
Abstract Recent work stresses a potentially important relation between credit supply shocks and aggregate TFP based on factor misallocation. I take three steps to examine this relation. First, using state-of-the-art credit supply shock and aggregate TFP measures, I show that an adverse credit supply shock has a weak and very short-lived effect on aggregate TFP. Second, using firm-level data, I show that firm-level capital stock responses to an adverse credit supply shock produce an insignificant and negligible capital-misallocation–induced TFP response. Third, using employment data by fine firm-size category classification, I also find a negligible labor-misallocation–induced TFP response. These findings suggest that the TFP channel of credit supply shocks has a limited role in their transmission to the real economy.